1983
DOI: 10.1177/104225878300800208
|View full text |Cite
|
Sign up to set email alerts
|

Management Practices of Successful Female Business Owners

Abstract: This research project examines management techniques used by 58 female owners of small businesses in three eastern metropolitan areas. Data indicate that financially successful women owners delegate certain key tasks to employees, are more highly educated, and have more prior work experience than less successful females. The primary inadequacies reported by the women were difficulties in leading others and inability to delegate tasks. In addition to a lack of formal planning and policy setting, other seemingl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
64
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(68 citation statements)
references
References 7 publications
3
64
1
Order By: Relevance
“…From 400 enterprises' data from three different industrial sectors, Kalleberg and Leicht [43] show that determinants of survival and success of enterprises in Indiana (USA) were independent from the owner's sex. Other studies having been carried out in developed countries have also shown that women's enterprises produce less incomes and even employ fewer workers than men's enterprises [25,49]. Even if it is accepted that there is a difference in women's and men'senterprises' output, Kalleberg and Leicht [43] estimate that this productivity difference is overestimated when one uses national data.…”
Section: Literature Review On Gender Productivity Differencementioning
confidence: 87%
“…From 400 enterprises' data from three different industrial sectors, Kalleberg and Leicht [43] show that determinants of survival and success of enterprises in Indiana (USA) were independent from the owner's sex. Other studies having been carried out in developed countries have also shown that women's enterprises produce less incomes and even employ fewer workers than men's enterprises [25,49]. Even if it is accepted that there is a difference in women's and men'senterprises' output, Kalleberg and Leicht [43] estimate that this productivity difference is overestimated when one uses national data.…”
Section: Literature Review On Gender Productivity Differencementioning
confidence: 87%
“…These differences seem to exist regardless of economic context. Previous studies have also shown that female business owners most often start businesses in the 'traditional' service sectors such as retail trade, hotels and catering (Schrier 1975;Smith, McCain & Warren 1982;Hisrich & Brush 1983;Cuba, Decenzo & Anish 1983;Scott 1986;Neider 1987;OECD 2000a;Du Rietz & Henrekson 2000). Studies of Sexton et al, 1990;Stigter, 1999, andVerheul &Thurik, 2001 have found that women have different objectives and ambitions than men, often interested in balancing their home and business responsibilities, and are less moved by profits or the size of their business.…”
Section: A Brief Review Of the Literaturementioning
confidence: 99%
“…Studies done in transitional economies such as Poland (Zapalska 1997) and Slovenia (Glas & Petrin 1998) have found that female business owners tend to be represented mostly in the service sector. In terms of business size and turnover, a number of studies have indicated that female-owned businesses tend to be smaller than male-owned businesses and have a lower business turnover (Schrier 1975;Schwartz 1976;Welsch & Young 1982;Geoffee & Scase 1983;Hisrich & Brush 1983;Chaganti 1986;Longstreth et al 1988;Smith et al 1982;Cuba et al 1983;Scott 1986;Neider 1987;Du Rietz & Henrekson 2000).…”
Section: A Brief Review Of the Literaturementioning
confidence: 99%
“…Other studies have shown that female business owners 4 most often start businesses that are in the 'traditional' service sectors such as retail trade, hotels and catering (Schrier 1975;Smith, McCain & Warren 1982;Hisrich & Brush 1983;Cuba, Decenzo & Anish 1983;Scott 1986;Neider 1987;van Uxem & Bais 1996;OECD 2000a;Du Rietz & Henrekson 2000). However, increasingly more female business owners are becoming involved in less traditional service sectors such as communications, finance, real estate, etc.…”
Section: Personal and Business Characteristics Of Male And Female Busmentioning
confidence: 99%
“…Studies done in economic transition countries such as Poland (Zapalska 1997) and Slovenia (Glas & Petrin 1998) have found that female business owners tend to be most prominently represented in the service sector. In terms of business size and turnover, a number of studies have indicated that female businesses tend to be smaller than male owned businesses and have a lower business turnover (Schrier 1975;Schwartz 1976;Welsch & Young 1982;Geoffee & Scase 1983;Hisrich & Brush 1986;Chaganti 1986;Longstreth et al 1988;Smith et al 1982;Cuba et al 1983;Scott 1986;Neider 1987;Du Rietz & Henrekson 2000).…”
Section: Personal and Business Characteristics Of Male And Female Busmentioning
confidence: 99%